SME’s GROWTH PATTERN AS A SUCCESS BUSINESS INDICATOR THROUGH SHARIA ECONOMIC IN REDUCING POVERTY IN INDONESIA - Meiria, Endah; Hamid, Abdul; Aishah, Riris (Archives of Business Research, 2019)
This study aims to explain and prove the correlation and the effect of the growth pattern of the SMEs (Small and Medium Enterprises) sector on the determinants of successful business through sharia economics and to determine the right variables in reducing poverty in Indonesia. The object of this research is poverty reduction variables and success business determinants in the tertiary sector of SMEs, namely services and trade. This study uses quantitative and qualitative methods, where the quantitative method uses random effect estimation method and the level of validity is tested using AR and JB tests. The expected results of this study are able to explain quantitatively and to prove the assumption of significant growth pattern of the micro small and medium enterprises sector to achieve a successful business through sharia economics on poverty reduction in Indonesia which has a positive correlation, in line with the assumption that successful SMEs through sharia economics also shows positive and significant results. This result will be analyzed qualitatively which is equipped with a foundation of fiqh.